Riley McGill: capstone - McGill, Riley, artist (Colorado State University. Libraries, 2023)
The artist's statement: In my fibers work,I focus heavily on instinctual process and experience - making quick decisions and doing what the piece feels it needs is crucial for me to truly and freely express myself and experience the materials I am working with. I go into my work with very little plan or attachment to the end goal, because I feel that this gives me much more freedom to act on instinct and natural expression, as well as build a deeper natural attachment and relationship to my work and materials. This instinctual and experiential process has lead me into the realm of abstract work, where quick decisions are key. Other key elements of my work are self expression, and the unexpected. I put and find myself into all of my work, and my art is a vehicle for me to find and make new and unique things that I like and that are personal and have obvious ties to myself and my personal style. It is important for all of my work to be able to be recognizable as mine,and working with an abstract, instinct-based process is the best way to naturally, and truthfully display myself and my style through my art. I like to have many colors, textures, small elements, and details to look at and discover, creating an exciting and engaging observer experience. Another thing I value highly in my work is repurposing materials. Most of my large-scale work includes unique materials I have found in my environment that would no longer have a use or home without being implemented into my work. I feel that this reuse of materials is not only important in a less-waste mindset, but it also breaths new and unique life into the materials and the work I am implementing them into.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers